Analysis Of Divers Satisfaction With Underwater Tourism in Ohoi Ngilngof Waters, Southeast Maluku Regency - Somnaikubun, Glenty B. A.; Rahajaan, Jusron Ali (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2024)
This research was conducted in Ohoi Ngilngof waters, precisely on Ngurbloat beach and Ohoieu Island. Research began in May 2024 to July 2024. The aim of this research was to analyze divers' satisfaction with underwater tourism in Ohoi Ngilngof waters and identify the attributes needed to improve tourism management Underwater in Ohoi Ngilngof waters, Southeast Maluku district. This research was carried out using observation and survey methods by distributing questionnaires to 42 divers who were determined using purposive sampling. Diver satisfaction is calculated using critical satisfaction analysis and the visitor satisfaction index (IPA). From the 5 dimensional data analyzed, divers were 100% satisfied with the Ohoi Ngilngof underwater tourism based on the satisfaction index, while based on the ISA analysis, of the 18 attributes analyzed there were improvements in the safety and comfort attributes of the ship. In addition, the number of diving groups needs to be changed immediately.